Evaluation of the effect of Gleditsia amorphoides gum on the properties of rennet-induced milk protein gels - Galante, Micaela (2019)
Fil: Galante, Micaela. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas; Argentina